2019
DOI: 10.3389/fimmu.2018.03136
|View full text |Cite
|
Sign up to set email alerts
|

Primary Immunodeficiency and Cancer Predisposition Revisited: Embedding Two Closely Related Concepts Into an Integrative Conceptual Framework

Abstract: Common understanding suggests that the normal function of a “healthy” immune system safe-guards and protects against the development of malignancies, whereas a genetically impaired one might increase the likelihood of their manifestation. This view is primarily based on and apparently supported by an increased incidence of such diseases in patients with specific forms of immunodeficiencies that are caused by high penetrant gene defects. As I will review and discuss herein, such constellations merely represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 350 publications
0
44
0
3
Order By: Relevance
“…While active adaptive immunity can lead to favorable clinical outcomes based on effective malignancy clearance, chronic inflammatory responses of innate immune cells in the vicinity of precancerous tissue may lead to tumorigenesis. Likewise, immune insufficiency can also result in increased cancer susceptibility, as seen in cases of primary immunodeficiency diseases [79], organ transplant-associated drug-induced immunosuppression [80], absence of immune cells including natural killer (NK), natural killer T cells (NKT), gamma delta (γδ) T cells, and other lymphocytes, or deficiency of immune products such as interferon-gamma (IFN-γ), perforins, and GM-CSF [81][82][83][84]. In this section, we discuss how cancer-associated biophysical cues influence immune cell phenotype through altered transcriptional and epigenetic programs (outlined in Fig.…”
Section: Biophysical Regulation and Epigenetics Of Immune Cells In Camentioning
confidence: 99%
“…While active adaptive immunity can lead to favorable clinical outcomes based on effective malignancy clearance, chronic inflammatory responses of innate immune cells in the vicinity of precancerous tissue may lead to tumorigenesis. Likewise, immune insufficiency can also result in increased cancer susceptibility, as seen in cases of primary immunodeficiency diseases [79], organ transplant-associated drug-induced immunosuppression [80], absence of immune cells including natural killer (NK), natural killer T cells (NKT), gamma delta (γδ) T cells, and other lymphocytes, or deficiency of immune products such as interferon-gamma (IFN-γ), perforins, and GM-CSF [81][82][83][84]. In this section, we discuss how cancer-associated biophysical cues influence immune cell phenotype through altered transcriptional and epigenetic programs (outlined in Fig.…”
Section: Biophysical Regulation and Epigenetics Of Immune Cells In Camentioning
confidence: 99%
“…The type of malignancy seems to be highly dependent on the specific PID, the age of the patient, and chronic infectious stimuli or dysbiosis involving complex pathogenic mechanisms (35). Cancer is 1.4 to 5-fold higher in registrybased PID studies respect to general population (36,37), from which 70% corresponds to lymphoid malignancy (38,39). Individuals with CVID are at 5 to 10-fold higher risk of developing hematological malignancies (36,37,40), while unexpectedly lower incidence on most common cancers than general population has been described (41,42).…”
Section: Sflc and The Dilema Between Primary And Secondary Immunodefimentioning
confidence: 99%
“…Cancer is 1.4 to 5-fold higher in registrybased PID studies respect to general population (36,37), from which 70% corresponds to lymphoid malignancy (38,39). Individuals with CVID are at 5 to 10-fold higher risk of developing hematological malignancies (36,37,40), while unexpectedly lower incidence on most common cancers than general population has been described (41,42). Cancer is a leading cause of mortality in PID, and thus early diagnosis and treatment of malignancy is a priority (22,43).…”
Section: Sflc and The Dilema Between Primary And Secondary Immunodefimentioning
confidence: 99%
“…Interestingly, the four most common cancers routinely occurred in men and women (lung, colon, breast, and prostate cancers) do not have significant elevation in subjects diagnosed with PID [31]. Evidence also demonstrated that patients with specific forms of immunodeficiency caused by highly penetrant gene defects have higher risk of developing cancer [32].…”
Section: Malignancymentioning
confidence: 99%